PECULIARITIES OF TLR9 EXPRESSION ON IMMUNE COMPETENT CELLS IN REACTIVE ARTHRITIS PATIENTS WITH CHRONIC EPSTEIN-BARR VIRUS INFECTION - Lomikovska, M.P.; Hayduchok, I.G.; Potomkina, H.O.; Zubchenko, S.O.; Kril, I.Y.; Ishcheykin, K.Y.; Chopyak, V.V. (World of Medicine and Biology, 2020)
The work presents the study findings on the TLR9 expression in immune competent cells in reactive arthritis patients with chronic Epstein-Barr virus infection, and considers the possibility of the reactive arthritis transformation into rheumatoid arthritis. It was established that expression of TLR9+CD123+ on monocytes was reliably higher in the blood of reactive arthritis patients as compared to healthy individuals, while in patients in active phase of EBV-infection the expression of this receptor was reliably higher as compared to similar indices of patients at the latent phase. At that, the number of TLR9+CD123+-monocytes in patients with reactive and rheumatoid arthritis was not reliably different. The number of TLR9+CD123+-lymphocytes as compared to indices of healthy individuals was reliably higher in patients with rheumatoid arthritis at both phases of chronic EBV-infection, while in patients with reactive arthritis it was only characteristic at the active phase of the infection. Expression of this receptor on lymphocytes turned out to be reliably higher in patients with rheumatoid arthritis as compared to patients with reactive arthritis, particularly at the active phase of chronic EBV infection.
Keywords: reactive arthritis; rheumatoid arthritis; chronic Epstein-Barr Virus Infection; TLR9